Vacuolar Sequestration of Paraquat Is Involved in the Resistance Mechanism in Lolium perenne L. spp. multiflorum - Brunharo, Caio A. C. G.; Hanson, Bradley D. (Frontiers in Plant Science, 2017)
Lolium perenne L. spp. multiflorum (Lam.) Husnot (LOLMU) is a winter annual weed, common to row crops, orchards and roadsides. Glyphosate-resistant populations of LOLMU are widespread in California. In many situations, growers have switched to paraquat or other postemergence herbicides to manage glyphosate-resistant LOLMU populations. Recently, poor control of LOLMU with paraquat was reported in a prune orchard in California where paraquat has been used several times. We hypothesize that the low efficacy observed is due to the selection of a paraquat-resistant biotype of LOLMU. Greenhouse dose-response experiments conducted with a susceptible (S) and the putative paraquat-resistant biotype (PRHC) confirmed paraquat resistance in PRHC. Herbicide absorption studies indicated that paraquat is absorbed faster in S than PRHC, although the maximum absorption estimates were similar for the two biotypes, indicating that differential foliar absorption of paraquat is not the cause of the resistance. Conversely, translocation of 14C-paraquat under light-manipulated conditions was restricted to the treated leaf of PRHC, whereas herbicide translocation out of the treated leaf was nearly 20 times greater in S. These results suggest that paraquat was either restricted to the apoplast or was compartmentalized within the plant cell but away from the chloroplast in PRHC. To determine whether paraquat was active within the plant cells, the photosynthetic performance was assessed after paraquat application using the parameter maximum quantum yield of photosystem II (Fv/Fm). Results indicated that paraquat reaches the chloroplasts of PRHC, since there was a transitory inhibition of photosynthetic activity in PRHC leaves. However, PRHC Fv/Fm recovered to initial levels by 48 hours after paraquat treatment. No paraquat metabolites were found, indicating that paraquat is stable in LOLMU plant cells and resistance is not likely due to paraquat degradation. LOLMU leaf segments were exposed to paraquat following pretreatments with inhibitors of plasma membrane- and tonoplast-localized transporter systems to selectively block paraquat intracellular movement. Subsequent evaluation of membrane integrity indicated that pre-exposure to putrescine resulted in the resistant biotype responding to paraquat similarly to S. These results strongly indicate that vacuolar sequestration is involved in the resistance to paraquat in this population of LOLMU.